2022
DOI: 10.3390/children9010052
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Weekday-to-Weekend Sleep Differences on Health Outcomes among Adolescent Students

Abstract: The sleep difference between weekdays and weekends can lead to negative physical and mental health outcomes in adolescents. Thus, this study has attempted to analyze the impact of sleep time differences on various health outcomes, using nationally representative panel data. Data from the junior high school student panel of the Korean Children and Youth Panel Survey were analyzed. The sleep difference was defined as the difference between the average sleep duration on weekdays and that on weekends in minutes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A previous study found that brief interventions in addressing health habits using a contract and/or a consultation strategy have the potential to influence positive changes in multiple health behaviors ( 15 ). Future research may want to focus on employing wellness interventions as well as investigations into the impact of weekday-to-weekend sleep differences on health outcomes among students, as it is found that the sleep differences can lead to negative mental health outcomes ( 53 ). Another recent study that performed a bidirectional relationship between sleep and depression demonstrated self-reported low sleep quality was a predictor of depression or depressive symptoms in college students ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that brief interventions in addressing health habits using a contract and/or a consultation strategy have the potential to influence positive changes in multiple health behaviors ( 15 ). Future research may want to focus on employing wellness interventions as well as investigations into the impact of weekday-to-weekend sleep differences on health outcomes among students, as it is found that the sleep differences can lead to negative mental health outcomes ( 53 ). Another recent study that performed a bidirectional relationship between sleep and depression demonstrated self-reported low sleep quality was a predictor of depression or depressive symptoms in college students ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weekday-to-weekend sleep time difference was used to measure participants’ sleep routine . A smaller sleep time difference is associated with better mental and (to a lesser extent) physical health [ 58 ]. The estimation of stationary sleep-segments was calculated using the OMGUI software (implementing the algorithm by Borazio et al [ 59 ]), upon which minutes of detected sleep between 9 p.m. and 11 a.m. were summed to become sleep time per night.…”
Section: Methodsmentioning
confidence: 99%
“…Teenagers also have a natural tendency to sleep later due to a typical sleep phase delay. The difference in sleep length between school days (weekdays) and non-school days (weekends) has been found to be associated with both mental health outcomes and physical health [10]. Those with less sleep variability have a lower risk of hypertension [11,12], obesity [13], and overall mortality [14].…”
Section: Introductionmentioning
confidence: 99%